Preparação de catalisadores Fe/FER e Fe2O3/FER: avaliação na redução de NO com CO - Soares, Magmir Metzker (Universidade Federal de São Carlos, 2012)
Due to the development of society, industrial processes and transportation (cars, buses, trucks, etc.) that emit pollutants are used, which affect the environment and consequently human health, flora and fauna. Among these contaminants, air pollution is the most complex, since it is becoming increasingly difficult to control, despite the efforts of more restrictive laws and the growing number of agencies for its regulation. Among the most worrisome issues stand out nitrogen oxides (NOx) generated throughout the combustion process of hydrocarbons. In the abatement of NOx, various catalytic processes are applied today. However, there is a need for them to be improved and upgraded, as to increase the activity and selectivity of the catalysts used for the conversion of NOx to N2. Thus, the air quality is preserved and the impacts of these contaminants in the environment are minimized. In this context, and considering the recent results in the literature and the Group of Catalysis UFSCar, this study aimed the preparation of catalysts based on cations Fen+ exchanged in zeolite ferrierite (|Nax| [SiyAlwOz]) or based on iron oxide supported and evaluated in the same reduction of NO to N2 by using CO as reducing agent. For purposes of comparison, catalysts were prepared based on commercial zeolites USY-type and mordenite under the same conditions of impregnation. Were also verified the effect of activity in the presence of O2, H2O(v) or SO2. The research included: i) preparation of ferrierite zeolite by ion exchange and impregnation of Mordenite and USY zeolite, ii) characterization via energy dispersive spectrometry of X-rays, atomic absorption spectroscopy, X-ray diffraction, scanning electron microscopy , diffuse reflectance spectroscopy in the ultraviolet visible reduction with H2 temperature-programmed and Mössbauer spectroscopy, iii) evaluating the reduction of NO with CO; iv) evaluation of the catalytic performance fronts interfering O2, H2O(v) and SO2. The catalytic tests showed that the samples with iron content close to 9% (FERtroca80 and FERimpr10) were the most active in the reduction of NO by using CO as reducing agent. The reaction was selective to the formation of desired products, even for high temperatures. The tests indicated that the sample interfering FERimpr10, which was more active in reducing the catalytic activity was not affected by the presence of SO2 or O2, being affected by the presence of O2 and H2O, which promoted a competition for active sites of the catalyst.
Keywords: Catálise heterogênea; Óxido nítrico; Monóxido de carbono; Óxido de ferro; Zeólita; ENGENHARIAS::ENGENHARIA QUIMICA